2014
DOI: 10.1016/j.visres.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Target frequency influences antisaccade endpoint bias: Evidence for perceptual averaging

Abstract: Perceptual judgments related to stimulus-sets are represented computationally different than individual items. In particular, the perceptual averaging hypothesis contends that the visual system represents target properties (e.g., eccentricity) via a statistical summary of the individual targets included within a stimulus-set. Here we sought to determine whether perceptual averaging governs the visual information mediating an oculomotor task requiring top-down control (i.e., antisaccade). To that end, participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 63 publications
2
16
1
Order By: Relevance
“…Notably, however, our group's (Gillen, Weiler, & Heath, 2013) quantitative analysis of Kapoula's data showed that her results provide no evidence for a range effect, and our work provided further evidence to support the overwhelming contention that prosaccades produce an invariant undershooting bias (Becker, 1989;Harris, 1995). What is more, the range effect is entirely incompatible with our group's previous work showing that antisaccades do not overshoot veridical target eccentricity regardless of the range and magnitude of target eccentricities included within a stimulus set (Gillen & Heath, 2014a;2014b).…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Notably, however, our group's (Gillen, Weiler, & Heath, 2013) quantitative analysis of Kapoula's data showed that her results provide no evidence for a range effect, and our work provided further evidence to support the overwhelming contention that prosaccades produce an invariant undershooting bias (Becker, 1989;Harris, 1995). What is more, the range effect is entirely incompatible with our group's previous work showing that antisaccades do not overshoot veridical target eccentricity regardless of the range and magnitude of target eccentricities included within a stimulus set (Gillen & Heath, 2014a;2014b).…”
Section: Discussioncontrasting
confidence: 60%
“…Instead, results support the contention that undershooting is an invariant control strategy designed to minimize energy expenditure (Becker, 1989) and/or saccade flight time (Harris, 1995;Gillen et al, 2013). Additionally, amplitudes were refractory to the different target-weighting conditions (see also Gillen & Heath, 2014b) and is a result demonstrating that absolute and retinotopically organized visual information mediates prosaccade sensorimotor transformations (Wurtz & Albano, 1980). In other words, the absolute visual information supporting prosaccades is incompatible with a SSR.…”
Section: Prosaccade Sensorimotor Transformations Are Mediated Via Abssupporting
confidence: 58%
See 2 more Smart Citations
“…antisaccades require the activation of an extensive frontoparietal network involved in the timeconsuming executive processes of response suppression and vector inversion (Munoz & Everling, 2004). Moreover, the smaller antisaccade gains (i.e., less accurate endpoints) indicate that decoupling the spatial relations between stimulus and response renders motor output that is supported via visual information that is functionally distinct (i.e., relative) from the direct (i.e., absolute) visual information mediating prosaccades (Gillen & Heath, 2014a;2014b;Heath, Gillen, & Weiler, 2015). These behavioural findings therefore provide a framework for examining executive and non-executive oculomotor dysfunction during the acute and later stages of concussion recovery.…”
Section: Pro-and Antisaccade Performance Metricsmentioning
confidence: 99%